2012
DOI: 10.5662/wjm.v2.i2.18
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing teamwork and collaboration within a tertiary medical center

Abstract: AIM:To understand how work climate and related factors influence teamwork and collaboration in a large medical center. METHODS:A survey of 3462 employees was conducted to generate responses to Sexton's Safety Attitudes Questionnaire (SAQ) to assess perceptions of work environment via a series of five-point, Likert-scaled questions. Path analysis was performed, using teamwork (TW) and collaboration (CO) as endogenous variables. RESULTS:Path analysis enables to identify statistically significant predictors of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 23 publications
1
6
0
3
Order By: Relevance
“…Regarding the indicator of self-assessment, the present study supported Stremmel and Powell (1991), Judge and Bono (2001) and Wu and Griffin (2012) who determined a significant relationship of self-assessment with JS. Similarly, the results of teamwork and collaboration established the findings of Makary et al (2006), Oandasan et al (2009), Oliver (2008), Chang et al (2009), Kalisch et al (2010) and Chien et al (2012) who posited that EI is positively related with JS. Furthermore, the results of optimism supported the findings of Lynn et al (1997), Al-Mashaan (2003), Kluemper et al (2009), Medline and Green (2009), and Kaplan and Bickes (2013).…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Regarding the indicator of self-assessment, the present study supported Stremmel and Powell (1991), Judge and Bono (2001) and Wu and Griffin (2012) who determined a significant relationship of self-assessment with JS. Similarly, the results of teamwork and collaboration established the findings of Makary et al (2006), Oandasan et al (2009), Oliver (2008), Chang et al (2009), Kalisch et al (2010) and Chien et al (2012) who posited that EI is positively related with JS. Furthermore, the results of optimism supported the findings of Lynn et al (1997), Al-Mashaan (2003), Kluemper et al (2009), Medline and Green (2009), and Kaplan and Bickes (2013).…”
Section: Discussionsupporting
confidence: 71%
“…Additionally, the results implied that university librarians probably feel happy at the workplace when they perform in teams and collaborate with each other. However, strong communication skills are needed to build successful collaboration within the team (Chien et al, 2012). Conversely, Ameen (2012) stated that communication courses, currently taught in LIS schools, are not supporting librarians to perform effectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Effective teams need a good communication process that involves the exchange of information and clear interaction between values, strengths and attitudes among team members, and that team members must often listen to each other to develop mutual knowledge and share information to enhance collaboration and communication [25]. A good work climate and job satisfaction positively influence teamwork [26].…”
Section: G Teamworkmentioning
confidence: 99%
“…Neufeld et al (2010) reported that effective personal communication skills are a central component of charisma that is critical in determining whether the leader's message will be understood and acknowledged, effective teams require reliable communication process that involves a clear exchange of information and interactions of values, powers and attitudes among team members, and that team members have to listen frequently to each other in order to develop mutual knowledge and information sharing to enhance collaboration and communication. Authors illustrated that a safe work climate and job satisfaction positively influence teamwork (Chien et al, 2012).…”
mentioning
confidence: 99%